The Appeal of Robotics to Children with Autism and Its Potential as a Therapeutic and Educational Tool - Avgousti, Sotiris; Vourkos, Eleftherios; Panayides, Andreas S.; Christoforou, Eftychios G.; Masouras, Panicos (My University, 2024)
This work examines the appeal of robotics to children with autism and the potential of using robots as a therapeutic and educational tool. A comparative experimental study was designed and implemented including three appropriately selected activities, one of which involved robots. The results provide further evidence regarding the positive role of robotics activities in special education and supports the idea of systematically exploiting these new possibilities, while investing in relevant scientific research.
Keywords: Educational robotics; Educational Robot Design and Programming; Robot-assisted therapy; STEM Disciplines; Special education